The Analysis of Secondary Motion and Lubrication Performance of Piston considering the Piston Skirt Profile. (27th March 2018) - Lu, Yanjun; Li, Sha; Wang, Peng; Liu, Cheng; Zhang, Yongfang; Müller, Norbert
Abstract : The work performance of piston-cylinder liner system is affected by the lubrication condition and the secondary motion of the piston. Therefore, more and more attention has been paid to the secondary motion and lubrication of the piston. In this paper, the Jakobson-Floberg-Olsson (JFO) boundary condition is employed to describe the rupture and reformation of oil film. The average Reynolds equation of skirt lubrication is solved by the finite difference method (FDM). The secondary motion of piston-connecting rod system is modeled; the trajectory of the piston is calculated by the Runge-Kutta method. By considering the inertia of the connecting rod, the influence of the longitudinal and horizontal profiles of piston skirt, the offset of the piston pin, and the thermal deformation on the secondary motion and lubrication performance is investigated. The parabolic longitudinal profile, the smaller top radial reduction and ellipticities of the middle-convex piston, and the bigger bottom radial reduction and ellipticities can effectively reduce the secondary displacement and velocity, the skirt thrust, friction, and the friction power loss. The results show that the connecting rod inertia, piston skirt profile, and thermal deformation have important influence on secondary motion and lubrication performance of the piston.